Impact of the Electrical Energy-Tariff and Vehicle-To-Grid in the Total Cost of Ownership of Electromobility Projects - Chavez-Orostica, H; Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper evaluates the impact of the electric power tariff on the total cost of ownership of electric vehicle purchase projects. Projects are analysed comparing electric vehicles with equivalent internal combustion engines vehicles. The annual equilibrium distance, Chilean energy tariffs, government incentives, and vehicle-to-grid utilities are considered in the analyses. Additionally, the current regulation in Chile is compared with special electrical vehicle energy tariffs applied in other countries is analysed to find possible spots to make electric vehicle projects more convenient. © 2021 IEEE.